2018
DOI: 10.1002/adom.201800338
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Information Encryption and Digital Display Applications Based on Multistate Smart Windows

Abstract: EC devices can be classified into following three types. [6,7] One of the most studied one involves conducting organic molecule based EC materials, which mainly contain conducting polymer and other conductive organic molecules. [8][9][10][11][12] These organic EC materials change their color mainly by modulating the composition of some functional groups through doping proton or other ions, thus resulting in their oxidized and reduced states. Another type includes the rare earths or their composites such as Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…[17] Consequently, it is evident that the advent of such devices reveals the significant ability of RMEDs to modulate light fluxes, thereby facilitating their application in solar radiation modulation. [75][76][77][78][79]…”
Section: Ag-based Rmedsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Consequently, it is evident that the advent of such devices reveals the significant ability of RMEDs to modulate light fluxes, thereby facilitating their application in solar radiation modulation. [75][76][77][78][79]…”
Section: Ag-based Rmedsmentioning
confidence: 99%
“…Previous reports have shown that RMEDs have a great ability to effectively modulate visible and IR radiation; however, the achievement of the separate control of the radiation originating from different spectrum regions presents a difficult but fascinating issue in the future. Finally, RMED is bound to exhibit its potential in thermal camouflage and thermal management of buildings, spacecrafts, and human bodies, as well as in light modulation for decreasing the power consumption of buildings, increasing the in-door and in-vehicle comfort, visible camouflage, and even information encryption [78] and holography. [96,97]…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…[ 5–10 ] Therefore, dual‐function devices have been reported to serve simultaneously as both electrochromic and energy storage devices. [ 11–14 ] In particular, electrochromic supercapacitors have been reported with excellent electrochemical performances and potentially real‐time indication of the energy level by their colors. [ 15,16 ] Moreover, the solar radiation transmittance can be modulated by electrochromic windows to control the room temperature, which is very promising for improving the energy efficiency of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic materials (ECMs) attract the close attention of researchers due to their applications in "smart" windows, [1][2] antiglare mirrors [3] and other "smart" electrochromic devices (ECDs) such as charge-indicators for batteries [4] and in wearable technologies. [5][6][7] This is a result of the colour-changing phenomena that occur from redox reactions when a potential is applied.…”
Section: Introductionmentioning
confidence: 99%